Hospital Based Emergency Care Systems in Thailand, 2007 - Sawanpanyalert, Narumol; Chomdej, Patcharin; Kanchanasut, Somchai (Journal of Health Science of Thailand, 2018)
While the demands on emergency and trauma care have grown dramatically, however, the capability of the system has been kept in check. The situation is creating a widening gap between the qualities of emergency care and the quality patients actually receive. Therefore, the operational research, covering 6 phases, has been conducted to develop the hospital-based emergency care system in Thailand during March 2006 - September 2007. Literature review of hospital emergency care at both national and international level was conducted followed by a survey on magnitude of problems of hospital emergency departments in Thailand. The survey results from 32 hospitals, selected by multistage stratified random sampling showed that manpowers and workloads were not compatible. After brain storming, a hospital-based emergency care system guideline was developed and implemented in 9 purposively selected hospitals. In general, the mean scores from all hospitals were 2.79-3.32 which were rated as quite good. However, the scores of supportive systems such as; information systems, quality management, and research and education were quite low. It is recommended that there should be a guideline on organizational structure of emergency department based on workloads and human resources. In addition, hospitals should specify clear role of emergency department, standard of information systems to be baseline data required for decision making. Furthermore, the consultation and referral center should be more effective.